Beyond authority leadership in a changing world - Middleton, Julia (Hampshire Palgrave Macmillian, 2007)
Many leaders have established their reputation in the internal silo environment of their organization. When they extend their leadership role beyond the organization, authority and legitimacy are constantly in question. Julia Middleton argues that new leaders need to be confident to legitimize themselves and challenge old ways. They need to develop a leadership style that will enable them to lead beyond the traditional boundaries and constraints of the organization. This book provides many challenging and compelling ideas and examples.
Includes bibliographical references and index.
Keywords: Leadership